Growing Plantation Forests - West, P. W.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book describes the scientific principles that are used throughout the world to ensure the rapid, healthy growth of forest plantations. As the population of the world increases so does the amount of wood people use. Large areas of natural forests are being cleared every year and converted to other uses. Almost as large an area of plantation forests is being established annually to replace those lost natural forests. Eventually, plantations will produce a large proportion of the wood used around the world for firewood, building, the manufacture of paper and bioenergy. Forest plantations can also provide various environmental benefits including carbon storage, rehabilitation of degraded land, serving as disposal sites for various forms of industrial or agricultural waste and enhancing biodiversity in regions that have been largely cleared for agriculture. Whatever their motivation, plantation forest growers want their plantations to be healthy and grow rapidly to achieve their purpose as soon as possible. This book discusses how this is done. It is written for a worldwide audience, from forestry professionals and scientists through to small plantation growers, and describes how plantations may be grown responsibly and profitably.
Plantation Forests -- Biology of Plantation Growth -- Growth Rates and Wood Quality -- Choosing the Species and Site -- Establishment -- Nutrient Management -- Stand Density and Initial Spacing -- Thinning -- Pruning -- Pests -- Diseases -- Tree Breeding -- 13 Mixed-Species Plantations -- Silviculture and Sustainability.
Keywords: Life sciences; Forests and forestry; Trees; Wood; Life Sciences; Forestry Management; Forestry; Tree Biology; Wood Science & Technology